2020
DOI: 10.1186/s12913-020-05807-0
|View full text |Cite
|
Sign up to set email alerts
|

When it rains, it pours: detecting seasonal patterns in utilization of maternal healthcare in Mozambique using routine data

Abstract: Background Climatic conditions and seasonal trends can affect population health, but typically, we consider the effect of climate on the epidemiology of communicable diseases. However, climate can also have an effect on access to care, particularly in remote rural areas of low- and middle-income countries. In this study, we investigate associations between the rainy season and the utilization of maternal health services in Mozambique. Methods We examined patterns in the number of women receiving antenatal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In our study, Maputo City was found to be the only city located in the southern region that provided effective access to three service packages investigated, which was consistent with previous ndings from other studies that 46% of pregnant women residing in southern Mozambique were able to access the nearest primary healthcare institute within 1-hour walking distance, while the other 64% of women living in the region were able to receive life-saving service delivery within 2 hours 35 . In addition, the frequent occurrence of natural disasters that posed huge hinderance to healthcare service delivery procedures further added to health inequity between southern and northern regions, leading to lower rates of both ANC and ID visits in the southern region, corresponding to 74 additional maternal deaths and 726 additional deaths of children under the age of 1 month by the end of 2021 37 . Under such circumstances, effective activities to address such inequity issue should include the implementation of decentralized allocation strategies, which has been recognized as an effective measure to facilitate the promotion of both accessibility and coverage of maternal health resources, thus contributing to higher hospital delivery rates as well as the reduction of both maternal and newborn mortality China's successful experience provides valuable lessons for other nations confronted with similar challenges 40 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, Maputo City was found to be the only city located in the southern region that provided effective access to three service packages investigated, which was consistent with previous ndings from other studies that 46% of pregnant women residing in southern Mozambique were able to access the nearest primary healthcare institute within 1-hour walking distance, while the other 64% of women living in the region were able to receive life-saving service delivery within 2 hours 35 . In addition, the frequent occurrence of natural disasters that posed huge hinderance to healthcare service delivery procedures further added to health inequity between southern and northern regions, leading to lower rates of both ANC and ID visits in the southern region, corresponding to 74 additional maternal deaths and 726 additional deaths of children under the age of 1 month by the end of 2021 37 . Under such circumstances, effective activities to address such inequity issue should include the implementation of decentralized allocation strategies, which has been recognized as an effective measure to facilitate the promotion of both accessibility and coverage of maternal health resources, thus contributing to higher hospital delivery rates as well as the reduction of both maternal and newborn mortality China's successful experience provides valuable lessons for other nations confronted with similar challenges 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Examining reporting over time was important for understanding reporting seasonality and changes to the health information systems relative to potential changes due to COVID-19. In countries with marked changes in climatic conditions, existing studies show that seasonal pattern exists between disease incidence (e.g., malaria, cholera, respiratory diseases) or health outcome and utilization of MCH services ( 26 28 ).…”
Section: Methodsmentioning
confidence: 99%
“…In that period there was reduction of around 6% less in maternal health service utilisation in all during rainfall season, except in the 2 biggest cities in the country (Maputo and Nampula) and 2 of the less populated provinces (Maputo and Niassa). (26) Despite 96% healthcare facilities having access to an ambulance for referrals, women identify lack of transport to bring women from the community to the healthcare facility as a major barrier to use of maternal care services in southern Mozambique. (27) We suggest that women's perception of 3rd phase delays in health facilities, lack of equipment, shortage of supervisors, irregular drug availability, absence of integration of care and lack of multidisciplinary teams as additional barriers at health system level.…”
Section: Care In Mozambiquementioning
confidence: 99%